PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PEMBIASAAN BERBASIS NILAI-NILAI ISLAM DI MADRASAH TSANAWIYAH - Agustin, Istikomah Yulfa; Rahmawan, Setia (FIKRAH, 2025)
The independent curriculum as an effort to improve the quality of Indonesian education gave birth to a new character education known as the Pancasila student profile. The Pancasila student profile answers the character problems of the nation's children in the current era. The aim of the Pancasila student profile is to produce students who have basic competencies and behavior that is in line with Pancasila values. Seeing this urgency, the cultivation of the Pancasila student profile is now starting to be carried out at various levels of education. This research is a descriptive study which aims to analyze the strengthening of the profile of Pancasila students through habituation activities based on Islamic values at Madrasah Tsanawiyah. The subjects of this research were teachers and students at MTsN 1 Yogyakarta. The data collection technique used was semi-structured interviews or in-dept interviews with informants as primary data and document studies as secondary data. The collected data will be analyzed using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this research show that efforts to strengthen the profile of Pancasila students can be done through habituation activities based on Islamic values. Habituation activities carried out consistently will shape the behavior and character of students in accordance with the six dimensions of the Pancasila student profile.